Preparation and Evaluation of Voriconazole as Topical Organogel - Hiba Muneer Fysal; Hanan Jalal Kassab (Iraqi Journal of Pharmaceutical Sciences, 2025)
Triazole antifungal drug voriconazole inhibits the fungal ergosterol synthesis and reacts very well against a wide range of fungal species. Organogel is a semisolid preparation in which the polar phase becomes immobilized within the three-dimensional structure. It would be ideal to have a topically applied form of voriconazole organogel to avoid undesirable systemic side effects and to reduce the dosage by coming into direct contact with the pathological site. This study aimed to formulate topical voriconazole organogel, consisting of a low molecular weight gelator (palmitic acid) at different concentrations with oleic acid, grape seed, and sesame oil. A solubility study revealed that voriconazole was highly soluble in the chosen oils. Several gelator concentrations were prepared by dissolving the drug in the oil at 85 °C, adding the gelator while continuously stirring for 40 minutes to obtain a clear solution, and then allowing the mixture to cool to room temperature to solidify. Formulas were prepared and evaluated based on their physical appearance, critical gelation temperature, spreadability, viscosity, pH, formulation, in vitro drug release study, antifungal study, and TEM. A compatibility study was conducted using Fourier-transform infrared (FT-IR) spectral analysis. An FT-IR study showed that the drug and excipients did not significantly interact. All the designed formulations of voriconazole show acceptable physical properties, pH, gel-solution, and solution-gel transition temperature. Viscosity and rheology studies demonstrated the pseudo-plastic shear thinning behavior of the organogels; among all formulations, palmitic acid with grape-seed oil at its critical gelation concentration (CGC) shows better drug release for sustained topical drug delivery; from the above observation results that this palmitic acid with grape-seed oil formulation might be a more promising topical treatment option for the recovery of skin fungal infections.